Synthesis of a 2D nitrogen-rich π-conjugated microporous polymer for high performance lithium-ion batteries. Issue 64 (22nd July 2019) - Meng, Lingkun; Ren, Siyuan; Ma, Chenhui; Yu, Ying; Lou, Yue; Zhang, Dong; Shi, Zhan
Abstract : Here we synthesized a 2D π-conjugated microporous polymerNGA-CMP . Heated sampleNGA-CMP400 is used for the first time as an anode for LIBs and shows high capacity lithium-ion storage with excellent cycle performance at high current density. Abstract : Novel 2D graphene analogues with high conductivity are highly demanded as anode materials for lithium-ion batteries (LIBs). Here we report the preparation and characterization of a π-conjugated microporous polymerNGA-CMP with an experimental bandgap of 2.34 eV. Heated sampleNGA-CMP400 is used for the first time as an anode material for LIBs.NGA-CMP400 achieves a high reversible capacity of 701 mA h g −1 at 1 A g −1 with extremely stable cycling performance over 500 cycles. The rational design of this kind of graphene-like 2D material with inherent porosity and enhanced electronic conductivity possesses important significance in carbon-based anode materials for LIBs.